Investigating Fundamental Football Skills of Extracurricular Athletes - Sahrizan, Rahmat; Suwirman, Suwirman; Arsil, Arsil; Arnando Nando, Muhammad (Universitas PGRI Palembang, 2025)
This investigation aimed to ascertain the baseline proficiency in fundamental football skills among a cohort of student-athletes (n=20) actively participating in the extracurricular football program at SMA Negeri 1 Sarolangun. Adopting a quantitative descriptive research paradigm, the current standing of essential football competencies was evaluated through the implementation of performance-based assessment protocols. These assessments specifically targeted key technical proficiencies, including passing-control, dribbling, shooting accuracy and power, and heading technique. Subsequent descriptive statistical analysis of the collected performance data revealed a